Analisis Pemanfaatan Insentif Pajak Pertambahan Nilai di Masa Pandemi Covid 19 di PT Hui Huang Media Masa Januari-Desember Tahun 2021 - Jiwa Pribadi; Kristiani Novia Adelina Nainggolan (JAMBIS : Jurnal Administrasi Bisnis, 2023)
In an effort to run a state, taxes are used to finance the public interest which in the end also includes the exclusive interests of individuals such as the interests of citizens, education, citizen welfare, community prosperity and so on. The purpose of this study is to analyze the Analysis of Utilizing Value Added Tax Incentives During the Covid 19 Pandemic at PT Hui Huang Media in January-December 2021. The research method used in this research is a qualitative descriptive method. The criteria for sources that the authors make as  informants  (parties/people  interviewed) in  this  study  are  parties  who  control  and understand the conditions of the research object, who are involved or occupy positions related to the topic under study and have enough time to be interviewed. The results of the study show that the use of Value Added Tax Incentives during the Covid 19 Pandemic at PT Hui Huang Media for the January-December 2021 period has been put to good use and has been implemented in accordance with the Regulations of the Governor of DKI Jakarta. In the event that there is a tax reduction regulation, it has been properly implemented with a VAT tax reduction. Fairness in the provision of tax incentives in reducing taxation is in accordance with the standards but is still not optimal, the impact arising from the regulations made has been implemented but not as expected